Afghanistan: The West fails - a win for China and Russia? The views from Beijing and Moscow - Sabine Fischer; Angela Stanzel (Stiftung Wissenschaft und Politik (SWP), 2021)
Russia and China are seen as the main beneficiaries of the Western withdrawal from Afghanistan regarding their political influence and potential exertion of power. In both the Chinese and Russian debate, however, alongside triumphant comments about Western failure, serious concerns about the regional security situation are being voiced. Western actors should seek a more nuanced understanding of Beijing's and Moscow's perspectives. This could also lead to opportunities for cooperation that would serve to stabilise Central Asia and Afghanistan. In view of the intensifying global systemic rivalry, however, the scope for cooperation will remain limited.
Keywords: 320